CERVICAL NEOPLASIA AND VIRUS LOAD OF HPV 16 GENOTYPE - V. S. Chirsky (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The 83 biopsies from HPV16-positive cervical epithelial neoplasies were studied by cytological, histological, immunomorphological methods and PCR. At cervical ectopia virus loading changed from 2.49 up to 6.65 lg copies of DNA HPV/105. At CIN II and CIN III the quantity of a virus exceeded 4 lg copies of DNA HPV/105 of cells, at the CIN I, Ca in situ and SCC — 5 lg copies of DNA HPV/105 of cells. At progressing of neoplasia frequency of revealing of clinically significant parameters of virus loading correlated with increase in average values of nuclear perimeter of cells, associated with HPV. At ectopia and LSIL expression of capsid protein L1 testified about virus production. At HSIL and SCC at absence expression L1 HPV high parameters of virus load testified to infringement of life cycle papillomaviruses.